INTERACTIVE INTERACTION AS ONE OF THE CONDITIONS OF EFFECTIVE ORGANIZATION OF THE TEACHING PROCESS IN HIGHER EDUCATION INSTITUTIONS - Revenko В.В. (Pedagogy of Higher and Secondary Education, 2022)
In the article the author makes the attempt to substantiste the essence of interaction, its kinds and mechanisms.